CSF proteomic profiling of mild cognitive impairment individuals with suspected non‐Alzheimer's disease pathophysiology: Developing topics. (7th December 2020) - Delvenne, Aurore; Gobom, Johan; Tijms, Betty M; Bos, Isabelle; Verhey, Frans RJ; Ramakers, Inez HGB; Scheltens, Philip; Teunissen, Charlotte E; Vandenberghe, Rik; Gabel, Silvy; Popp, Julius; Peyratout, Gwendoline; et al.
Abstract: Background: Suspected non‐Alzheimer's disease pathophysiology (SNAP) is a biomarker‐defined concept that encompasses individuals with Alzheimer's disease (AD) neuronal injury but without amyloidosis. We have previously shown that 24% of mild cognitive impairment (MCI) individuals with SNAP will progress within 3 years to the AD dementia stage. Nonetheless, it remains unclear what explains the MCI‐SNAP biomarker profile and whether it reflects an early stage of AD, atypical AD or non‐AD pathology. We aimed to investigate the underlying pathophysiology of MCI‐SNAP using proteomics in cerebrospinal fluid (CSF). Method: We included 206 individuals from the European EMIF‐AD MBD study and Maastricht BB‐ACL study. Based on CSF Aβ1‐42 (A) and p‐tau (T), individuals were classified as cognitively normal with normal A and T (CN, n=100), MCI with normal A and abnormal T (MCI‐SNAP, n=32), and MCI with abnormal A and T (MCI‐AD, n=74). We centrally generated CSF proteomic data for 1761 proteins using tandem tag mass spectrometry. We compared protein concentrations between groups using ANOVA adjusted for age and sex (1/3 observations per group minimum). We performed Gene Ontology enrichment analyses with false discovery rate to uncover the biological pathways of MCI‐SNAP. We investigated the expression profile of proteins in fetal/mature astrocytes, neurons, oligodendrocytes, microglia and endothelial cells. Result: Sample characteristics are presented in Table 1. In MCI‐SNAP, we found 83 decreased and 28 increased proteins compared to CN and 177 decreased and 21 increased proteins compared to MCI‐AD. In MCI‐AD, we found 13 decreased and 193 increased proteins compared to CN. Proteins with decreased levels in MCI‐SNAP compared to both CN and MCI‐AD (n=55) were enriched for extracellular matrix, hemostasis, immune system, proteolysis and lysosome (Figure 1). A high percentage of these decreased proteins in MCI‐SNAP are expressed by mature astrocytes (51%) and endothelial cells (49%). Proteins increased in MCI‐SNAP and MCI‐AD compared to CN (n=17) were related to cytoskeleton organization and mainly expressed by neurons (88%). Conclusion: Our results show that the pathophysiology of SNAP is distinct from that of AD. Further studies are needed to clarify the role of extracellular matrix, hemostasis, immune system, proteolysis and lysosome processes in SNAP.